KEBEBASAN BERAGAMA DALAM PANDANGAN AL-QUR’AN: KOMPARASI TAFSIR KLASIK-KONTEMPORER - Galela, Afrizal; Sumbulah, Umi; Mubarak, Ruma (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Religious freedom is a crucial issue that continues to evolve in an increasingly complex global world. This study presents an in-depth analysis of spiritual freedom in the Qur’an through a comparative approach between the interpretations of classical scholars and contemporary exegetes. This study departs from the central question: how is the Qur’an’s view of religious freedom interpreted by classical and modern exegetes, and to what extent do differences in socio-historical contexts influence these interpretations?. Through a comprehensive literature study, we explore how classical interpretations, often considered rigid, interact with more progressive contemporary interpretations, creating innovative dialogue and valuing diversity. This study not only reveals gaps in current understanding but also offers bold solutions to the challenges of religious freedom in the modern era. Our findings show that embracing new perspectives can create a stronger foundation for pluralism and tolerance in society. By presenting these paradigm-shifting insights, this research has the potential to be a turning point in academic discussions and policy practices related to religious freedom.